Etika Dakwah dalam Al-Qur'an dan Hadits - Khoirurroji'in (International Journal of Publication Unit (IUJP) Agus Salim Metro, 2019)
Abstract The concept of da'wah is not only related to the problem of how to speak effectively but also the ethics of speech. Since entering the era of reform, Indonesian society has been in a state of euphoria, free to talk about anything, to anyone, in any way. Al-Qur'an refers to speaking as one of human nature. Especially when discussing or delivering religious law. Although the edited command was edited to the Prophet, but the message contained in the verse can be generally applied to every Muslim who undertakes deliberation or preaching. It is required in the verse about the attitude that must be done to succeed in deliberation or in delivering religious law, preaching at its origin it is difficult to be accepted by the souls of infidels, when delivered in a bad way, a rude way, of course it will only make people run away from the truth (da'wah). For this reason, da'wah basically must be conveyed in a gentle way.